Kajian Sistematis Efek Empiris, Farmakologis dan Klinis Terapi Kelor (Moringa oleifera Lam.) - Willie Japaries; Yelini Fan Hardi; Frisca Desma Ayu (STIKes Ibnu Sina Ajibarang, 2023)
Background: Kelor or drumstick tree (Moringa oleifera Lam.) is a widely known foodstuff and traditional medicine in many Asian countries including Indonesia. Methodology: This article is a systematic review of scientific studies’ results about Kelor extracted from database Sciencegate, PubMed dan CNKI within the last 10 years. Results: Kelor as a traditional medicine has been utilized since thousands of years ago in India and Egypt. In traditional medicine it is used to treat wounds, ulcers, pains, diseases of the liver, heart, cancer, etc. Studies have indicated it contains a complete nutritional substances and can be used to treat malnutrition among women and children. Active substances in Kelor have been proven to possess antioxidant, anti-inflammatory, antibacterial, antiviral, antidiabetic, anti-atherosclerotic effects. Conclusion: Kelor’s leaves and seeds have been proven scientifically to be safe and effective for nutrition supplementation for women and children, and potential as therapy against various diseases suffered by the society nowadays such as diabetes, hyperlipidemia, rheumatoid arthritis, etc.